The impact of openness on human capital: A study of countries by the level of development - Dao Thi Bich Thuy; Quy Van Khuc (Economies, 2023)
This study investigates the impact of openness on human capital in 112 countries worldwide in 2000-2019. An two-stage least square fixed-effect model with instrumental variables is used to unravel the complicated relationship between human capital and its key determinants. The empirical results show that the impacts of openness vary greatly among different groups of countries. For example, while FDI has no effect on human capital in developed and upper-middle-income developing countries, its effect is positive in lower-middle-income countries and negative in low-income countries. Exports stimulate human capital formation in developed countries but in low-income developing countries, they act as an impediment to human capital formation. Imports have a positive effect on human capital in developing countries; however, in developed countries, the effect of imports on human capital is negative. International cooperation effectively raises the level of human capital in developed, upper-middle-income and low-income countries; however, it has no effect in lower-middle-income countries. In light of mindsponge-mindspongeconomics and the SM3D knowledge management system, the study's findings particularly shed light on the long-term development roadmap associated with human capital and openness expansion in less developed and emerging countries in years to come.
Keywords: 330; openness; human capital; mindspongeconomics; mindsponge; SM3D; developed and developing countries